Institutions and training inequality - Wolfgang Lechthaler; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
We analyze the interaction among important institutional variables in the labor market (firing costs, minimum wages and unemployment benefits) in determining firm-provided training. We find that the institutional interactions - specifically, their degree of complementarity and substitutability - depends on employees' abilities. On this account, the institutional interactions influence skills inequality. We derive how the influence of one of the institutional variables above is affected by other institutional variables with respect to inequality skills arising from firm-provided training. We derive several striking results, such as: (a) the minimum wage and unemployment benefits generate increasing skills inequality whereas firing costs generate diminishing skills inequality; (b) unemployment benefits and firing costs are complements in their effects on skills disequalization, (c) firing costs and the minimum wage are complements in their effects on skills equalization, and (d) unemployment benefits and the minimum wage are substitution in their effects on skills inequality.
Keywords: H32; J24; 330; Skills Inequality; Institutions; Firm Training; Betriebliche Weiterbildung; Betriebliche Bildungsarbeit; Qualifikation; Bildungschancen; Kündigungsschutz; Mindestlohn; Arbeitslosenversicherung; Theorie